A New Fuel Design for Two Different HW Type Reactors - Brasnarof, Daniel Oscar (2011)
A new fuel element (called CARA) designed for two different heavy water reactors (HWRs) is presented. CARA could match fuel requirements of both (one CANDU and one unique Siemens's design) Argentine HW reactors. It keeps the heavier fuel mass density and hydraulic flow restriction in both reactors together with improving both thermomechanic and thermalhydraulic, safety margins of present fuels. In addition, the CARA design could be considered as another design line for the next generation of CANDU fuels intended for higher burnup.